Estimating the Local Effectiveness of Institutions: A Latent-Variable Approach - Antonia Reinecke; Hans-Jörg Schmerer (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper develops an approach that allows constructing regional proxies of government effectiveness at a highly dis-aggregated level. Our idea builds on the well documented interdependence between institutions and exports, which allows estimating the latent government effectiveness using methods of structural equation modeling. Unobserved institutional quality for each individual region is predicted using the regression outcomes. The impact of this novel identification strategy is tested using various panel applications. Results show that the magnitude of the effect of institutional quality can be biased in estimates that neglect regional differences in the effectiveness of institutions.
Keywords: D02; F10; P16; 330; trade; institutions; Chinese plant data; latent variable; structural equation modelling